Feasibility, potency, and safety of growing human mesenchymal stem cells in space for clinical application - Huang, Peng (NPJ Microgravity, 2020)
Growing stem cells on Earth is very challenging and limited to a few population doublings. The standard two-dimensional (2D) culture environment is an unnatural condition for cell growth. Therefore, culturing stem cells aboard the International Space Station (ISS) under a microgravity environment may provide a more natural three-dimensional environment for stem cell expansion and organ development. In this study, human-derived mesenchymal stem cells (MSCs) grown in space were evaluated to determine their potential use for future clinical applications on Earth and during long-term spaceflight. MSCs were flown in Plate Habitats for transportation to the ISS. The MSCs were imaged every 24–48 h and harvested at 7 and 14 days. Conditioned media samples were frozen at −80 °C and cells were either cryopreserved in 5% dimethyl sulfoxide, RNAprotect, or paraformaldehyde. After return to Earth, MSCs were characterized to establish their identity and cell cycle status. In addition, cell proliferation, differentiation, cytokines, and growth factors’ secretion were assessed. To evaluate the risk of malignant transformation, the space-grown MSCs were subjected to chromosomal, DNA damage, and tumorigenicity assays. We found that microgravity had significant impact on the MSC capacity to secrete cytokines and growth factors. They appeared to be more potent in terms of immunosuppressive capacity compared to their identical ground control. Chromosomal, DNA damage, and tumorigenicity assays showed no evidence of malignant transformation. Therefore, it is feasible and potentially safe to grow MSCs aboard the ISS for potential future clinical applications.